Urban School Climate (USC): The Study of Teacher Perceptions of Safe and Comfortable School Atmosphere in Elementary School - Fauziah, R. Siti Pupu; Kartakusumah, Berliana; Suherman, Irman (Universitas Djuanda, 2024)
Building child-friendly schools is teachers' main task so students can learn safely and comfortably. However, there are still teachers who still need to be fully aware of this. This research aims to explore elementary school teachers' perceptions of a safe and comfortable environment as an illustration of the Urban School Climate (USC). This research method is a case study with a qualitative approach. Interviews with elementary school teachers in Bogor carried out data collection. Conversations are carried out directly (face-to-face) and are recorded to ensure that the interview results match the respondent's information. Our research involved 45 teachers with permanent teacher (PT) status in 17 elementary schools in Bogor, Indonesia. The recruitment of teachers who would share their valuable insights was carried out using a purposive sampling technique. Data analysis was carried out using the Miles and Huberman model, including data reduction, display, and verification. The data analysis was assisted with Nvivo 12 software. The research results showed a safe and comfortable environment as an illustration of USC, including 1) a pleasant school atmosphere for students and teachers, adequate facilities and a mutually supportive atmosphere, 2) a safe environment, 3) a comfortable environment, and 4) school policies which lead to restrictions for parents when picking up their children at school, regulations regarding discipline and various binding regulations. The impact of the results of this research is that schools can build a school climate by referring to the characteristics of USC, which are described as a safe and comfortable school atmosphere and environment.